Improved efficiency of bulk heterojunction polymer solar cells by omitting electron transport layer: a SCAPS 1D simulation study - C. D., Ramabadran; N P, DHANYA; Sudheer Sebastian, (Vietnam Journal of Science and Technology, 2025)
In this work we analyse the role of bulk heterojunction polymer solar cells (BHJPSCs) in the field of photovoltaics. Specifically, we investigate the performance of a BHJPSC setup eliminating the electron transport layer (ETL). With the aid of SCAPS 1D software, we conduct simulation studies to evaluate the effectiveness of this innovative approach. Initially, we standardized the program by replicating a key experimental study that used P3HT:IC60BA as the active layer, producing results consistent with actual observations. We studied the solar cell structure ITO/PEDOT:PSS/P3HT:IC60BA/ZnO NPs/Al, where we achieve an efficiency of 3.97% through standard procedures. Interestingly, by removing the ETL in our simulations leads to a substantial efficiency of 10.83% after optimization. This improved efficiency highlights the potential of our method, further investigation and optimization of BHJPSC configurations without ETL for enhanced photovoltaic performance may lead to better results